2014
DOI: 10.3390/molecules19056891
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miRNAs as Biomarkers for Neurodegenerative Disorders

Abstract: Abstract:Neurodegenerative disorders, such as Alzheimer's disease (AD), Parkinson's disease (PD) and frontotemporal dementias (FTD), are considered distinct entities, however, there is increasing evidence of an overlap from the clinical, pathological and genetic points of view. All neurodegenerative diseases are characterized by neuronal loss and death in specific areas of the brain, for example, hippocampus and cortex for AD, midbrain for PD, frontal and temporal lobes for FTD. Loss of neurons is a relatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
128
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(130 citation statements)
references
References 100 publications
0
128
0
2
Order By: Relevance
“…Epigenetic changes in blood are relevant even if they do not capture all changes observed in organ-specific tissue [100]. An increasing number of studies have demonstrated that levels of circulating miRNAs released by cells into the bloodstream are correlated with tissue miRNA levels [101,102]. Another limitation with use of blood specimens is that cell-type heterogeneity can act as a source of bias if cell-type proportions are associated both with miRNA expression levels and sex.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic changes in blood are relevant even if they do not capture all changes observed in organ-specific tissue [100]. An increasing number of studies have demonstrated that levels of circulating miRNAs released by cells into the bloodstream are correlated with tissue miRNA levels [101,102]. Another limitation with use of blood specimens is that cell-type heterogeneity can act as a source of bias if cell-type proportions are associated both with miRNA expression levels and sex.…”
Section: Discussionmentioning
confidence: 99%
“…A number of new medical methods are being designed for early diagnosis in the most important mental pathologies and neurodegenerative diseases: new biochemical and molecular detectors, EEG, neuroimaging, ocular-macular exploration, pupillometry, exercise and gait analysis, equilibrium platforms, manual exercises, cognitive trials, memory tests, linguistic trials, etc. [27,35,[38][39][40][41]. We think laughter could also be added to that list of biomedical explorations.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs serve a role in nervous system diseases, including autoim mune neuroinf lam mation (13), Alzheimer's disease (14) and Parkinson's diseases (15). A previous study indicated that the expression of miR-124 was downregulated in newborn rats with thyroid hypofunction (19).…”
Section: Discussionmentioning
confidence: 99%
“…Binding of miRNA to the 3' untranslated region (UTR) may degrade target mRNA and block translation (12). Previous studies have suggested the role of miRNAs in nervous system diseases, including autoimmune neuroinflammation (13), Alzheimer's disease (14) and Parkinson's disease (15). miR-124-3p may also attenuate matrix metalloproteinase-induced neuronal injury via regulating signal transducer and activator of transcription 3 expression in SH-SY5Y cells (16).…”
Section: Introductionmentioning
confidence: 99%